2019
DOI: 10.3389/fcell.2019.00052
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the Head and Neck Squamous Cell Carcinoma Immune Landscape and Its Impact on Immunotherapy

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are highly aggressive, multi-factorial tumors in the upper aerodigestive tract affecting more than half a million patients worldwide each year. Alcohol, tobacco, and human papillomavirus (HPV) infection are well known causative factors for HNSCCs. Current treatment options for HNSCCs are surgery, radiotherapy, chemotherapy, or combinatorial remedies. Over the past decade, despite the marked improvement in clinical outcome of many tumor types, the overall 5-year s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
211
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(230 citation statements)
references
References 149 publications
(311 reference statements)
1
211
0
1
Order By: Relevance
“…Thus, the miR-142-3p upregulation described in certain cancers may be due to the presence of immune cells in tissue homogenates, which can only be distinguished by single-cell sequencing or in situ analysis. This, as well as the specific immune cell types expressing miR-142-3p, should be considered in future analyses, and those ascribing biomarker function to miR-142-3p should determine if it is a tumor cell-autonomous biomarker, a general marker of inflammation, or a marker of specific tumor-associated immune cell states, the latter of which could have implications for sensitivity to immunotherapy [107].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the miR-142-3p upregulation described in certain cancers may be due to the presence of immune cells in tissue homogenates, which can only be distinguished by single-cell sequencing or in situ analysis. This, as well as the specific immune cell types expressing miR-142-3p, should be considered in future analyses, and those ascribing biomarker function to miR-142-3p should determine if it is a tumor cell-autonomous biomarker, a general marker of inflammation, or a marker of specific tumor-associated immune cell states, the latter of which could have implications for sensitivity to immunotherapy [107].…”
Section: Discussionmentioning
confidence: 99%
“…HNSCCs can severely impact the quality of life of patients while have poor prognosis, low responsiveness to treatment, and drug resistance. HNSCC malignancy has a high morbidity and mortality rate since only 50% to 60% of patients have a survival rate of 5 years after diagnosis of HNSCC, and up to 30% of patients develop cancer relapse and treatment failure 6 . It has been found that one of the most imperative prognostic determinants of the survival rate from HNSCC is the presence of lymph node metastases 7 …”
Section: Overview Of Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…In addition, half of the independent HNSC data set was HPV positive (HPV+). HPV+ oropharyngeal squamous cell carcinomas are very different to HPVoropharyngeal carcinomas [25], and they have distinct methylation patterns [26]. The HPV status of the TCGA data is unknown, but as HPV+ tumours are seen more frequently in the oropharynx than other tissues of origin and only a small fraction of the TCGA data is from the oropharynx, it is likely that a very small fraction of the training data was HPV+.…”
Section: Discussionmentioning
confidence: 99%